The outcome of different β lactamase production in Klebsiella pneumoniae subspecies pneumoniae isolated from different clinical specimen in tertiary care hospital: a study - Singh, Priyanka (International Journal of Research in Medical Sciences, 2018)
Background: Klebsiella pneumoniae subspecies pneumoniae is one of the most commonly isolated bacterial species in Microbiology laboratories and can cause Infection in hospitalised patients with strain resistant to many antimicrobials. Klebsiella pneumoniae is more frequently recovered from clinical specimen. The carrier rate as high as 20% may occur in hospitalized patient. Methods: Isolates are screened for presumptive ESBL by reduced susceptibility to CAC, CAZ, Carbapenemase by Classical Hodge test and modified Hodge test, MBL by DP Test, AmpC production by testing their susceptibility to Cefoxitin using Kirby-Bauer disk diffusion method. KPC by combined Disc method using PBA. Results: Out of total 300 Klebsiella pneumoniae strains studied, 98 (32.7%) were isolated from urine followed by pus and wound swab 74 (24.7%) and 63 (21%) were isolated from blood. Conclusions: Maximum (23.5%) ESBL, (10.2%) AmpC β- lactamases and (10.2%) KPC producing strains were isolated from urine sample. Maximum 32.1% MBL producing Klebsiella pneumoniae strains were isolated from pus and wound swab.